Blood Lactate Level as Predictor of Early Outcome after Off-Pump Coronary Artery Bypass Grafting (Cardiovascular Journal, 2020)
Background: Identification of predictors of morbidity and mortality is an important issue for the management of cardiac surgical patients. Elevated lactate concentrations in the immediate postoperative period reflect unmet metabolic demand and may be associated with outcome.Methods: A prospective observational study was carried out in the department of cardiac surgery, at National Heart Foundation Hospital& Research Institute(NHFH&RI), Dhaka. commencing from July 2016 to March 2018. In all Adult patients irrespective of sex undergoing elective off-pump coronary artery bypass grafting (OPCABG). Purposive sampling was applied with patient with blood lactate level < 3 mmol/L 6hours after shifting from OT to ICU in Group-A and blood lactate level ≥3mmol/l, 6hours after shifting to the ICU in Group-B.Postoperative early adverse outcomes were analyzed in both the patient groups.Results: Blood lactate level 6 hours after ICU transfer is an independent predictor for prolonged mechanical ventilation time, (OR 2.540, 95% CI 1.781-3.621, p=